Tourist demand towards Thai Song Dam Ethnic Tourism Central Province Group - Nantakit , Siripa; Wongmonta, Seri (Journal of Humanities and Social Sciences, Rajapruk University, 2022)
This research aims to: 1) Study the personal attributes and behavior of tourists as well as their needs towards ‘Thai Song Dam’ ethnic tourism in the Central Provinces region. 2) Compare the needs of tourists towards ‘Thai Song Dam’ ethnic tourism of the Central Provinces region, classified by the tourists’ personal characteristics, and behaviors, and 3) Study the relationship between personal attributes and travel behavior of Thai Tourists. Focus on the ‘Thai Song Dam’ ethnic tourism attractions of the central provinces region. The research collected information from 400 Thai tourists who traveled to the central provinces region and visited the ‘Thai Song Dam’ ethnic tourism attractions. The methodology used for this research was data collection from questionnaires. The data were analyzed with statistical analysis for frequency, mean, standard deviation, t-test F-test, and LSD Square and Cramer’s-V values. The results showed that: 1) The majority of tourists are male aged between 20-29 years old with education below a bachelor’s degree, self-employed, single with a monthly income between 15,001-20,000 Baht, and domicile in the central/perimeter regions of Thailand. Thai tourists travel with the intention of rest and relaxation. They travel with families and relatives during Saturday-Sunday and public holidays. Their total trip average expenses are less than 2,000 Baht. The majority travel within Phetchaburi Province in groups of 4-5 people and make a trip in less than 3 months/time. Thai tourists like local cultural attractions and they search for travel resources from online media. There is a demand from Thai tourists for promotion guidelines for ‘Thai Song Dam’ ethnic tourism of the central provinces region. Overall the average of the highest level of demand was the process of organizing ethnic tourism activities. The average is also at a high level on product aspects, price aspects, distribution channels, marketing promotions, sales personnel, tourism attractions, business cooperation, and ethnic tourism promotion by the government. 2) The various personal attributes and behaviors of tourists have a different levels of demand towards promotion guidelines of the ‘Thai Song Dam’ ethnic tourism of the central provinces region. And 3) Thai tourists’ personal attributes have related to low to medium level of Thai tourism behavior towards ‘Thai Song Dam’ ethnic tourism in the central provinces region.